Right to information on a broad canvas (Note) - Joseph, Vinod (2001)
After a series of promises to enact a law on right to information, a draft bill on right to information, a draft bill on freedom of information has come into being. The article brings out various aspects and inadequacies of the bill suggesting improvements towards a meaningful devolution of the information to the grass-roots level. - Reproduced
Keywords: Note; Right to information